Голод на Україні 1932–1933 рр. (за документами польських дипломатів) - Кусьнєж, Р. (Архіви України, 2008)
The publication of the Polish researcher of the 1932–1933 Famine in Ukraine covers the documents of the Polish diplomatic missions in Ukraine and Moscow, which display the then situation in agriculture and the people’s miserable living in Bolshevist Ukraine. The given documents from the Polish archives testify to artificial destruction of Ukrainian agriculture, which resulted in the terrible famine of Ukrainian peasantry and, consequently, huge amount of those starved to death – at least, 3 ml people.